1993
DOI: 10.1002/j.1460-2075.1993.tb05740.x
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of the light signal during complementary chromatic adaptation in the cyanobacterium Calothrix sp. PCC 7601: DNA-binding proteins and modulation by phosphorylation.

Abstract: The cyanobacterium Calothrix sp. PCC 7601 can adapt its pigment content in response to changes in the incident light wavelength. It synthesizes, as major light‐harvesting pigments, either phycocyanin 2 (PC2, encoded by the cpc2 operon) under red light or phycoerythrin (PE, encoded by the cpeBA operon) under green light conditions. The last step of the signal transduction pathway is characterized by a transcriptional control of the expression of these operons. Partially purified protein extracts were used in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 34 publications
(24 reference statements)
3
52
0
Order By: Relevance
“…These mutants exhibit normal regulation of cpcB2A2 but cannot activate cpeBA in GL. Complementation of the FdTq strains uncovered two genes, trqA and trqB, encoding polypeptides related to protein phosphatases 3 ; this finding is interesting, especially because phosphorylation of the putative regulatory protein RcaA has been implicated in the control of cpeBA expression (21).…”
Section: Complementary Chromatic Adaptationmentioning
confidence: 94%
“…These mutants exhibit normal regulation of cpcB2A2 but cannot activate cpeBA in GL. Complementation of the FdTq strains uncovered two genes, trqA and trqB, encoding polypeptides related to protein phosphatases 3 ; this finding is interesting, especially because phosphorylation of the putative regulatory protein RcaA has been implicated in the control of cpeBA expression (21).…”
Section: Complementary Chromatic Adaptationmentioning
confidence: 94%
“…PTMs participate in numerous biological processes in cyanobacteria, such as circadian rhythms [29,30], global carbon/nitrogen control [31], nitrogen fixation [32], complementary chromatic adaptation [33,34]. PTM events are also reported to exist in photosynthesis apparatus, including photosystem I [35], photosystem II [36], phycobiliproteins [37,38] and cytochrome b6f complex [39].…”
Section: Ptm Studies In Cyanobacteriamentioning
confidence: 99%
“…However, recently, comprehensive functional analyses have revealed that Ser/Thr/Tyr kinases and phosphatases play vital roles in regulating many critical processes in cyanobacteria, such as stress adaptation, cell differentiation, cell motility, carbon and nitrogen metabolism and photosynthesis [63]. The number of genes encode putative Ser/Thr/Tyr kinases range from none to 52 in the fully sequenced cyanobacteria strains [63], suggesting that both the two phospho-based signaling systems are important in cyanobacteria [34,39].…”
Section: Phosphoproteomementioning
confidence: 99%
“…The genes involved in this adap= tive response have been mapped and the information available on gene activation occurring in CCA (Federspiel and Grossman 1990), including phosphorylationdependent binding of activator protein in the promoter area of genes encoding antenna polypeptides (Sobczyk et al 1993), suggests the involvement of a Twocomponent signal transduction system, for which a sensor protein has been identified via complementation analysis of CCA-deficient mutants (Chiang et al 1992). The protein identified in this complementation, RcaC, ishows similarities with other sensor proteins of Two-component family.…”
Section: Regulation In Chromatic Adaptation: a Bacterial Rhodopsinmentioning
confidence: 99%